Respuesta :
Answer:
[tex]\sqrt{13}[/tex]
Step-by-step explanation:
The trick here is to know the distance formula (a formula that helps you find the distance between two points).
Distance formula: distance = [tex]\sqrt{(x_2-x_1)^2+(y_2-y_1)^2}[/tex]
But now that we know this, we can simply plug in our values and solve!
[tex]\sqrt{(x_2-x_1)^2+(y_2-y_1)^2}\\\sqrt{(6-3)^2+(5-7)^2}\\\sqrt{(3)^2+(-2)^2}\\\sqrt{9+4}\\\sqrt{13}[/tex]
Now we can tell from our answer that the distance between both points is [tex]\sqrt{13}[/tex]
We know that the distance between two points (x₁, y₁) and (x₂, y₂) is given by:
[tex]d = \sqrt{(x_2 - x_1)^2 + (y_2 - y_1)^2}[/tex]
Only with this, we can find that the distance between the two given points is [tex]\sqrt{13} = 3.606[/tex]
Now let's see the operation:
In this particular case, we want to find the distance between the points E(3, 7) and F(6, 5), replacing these in the above equation we get:
[tex]d = \sqrt{(3 - 6)^2 + (7 - 5)^2} = \sqrt{3^2 + 2^2} = \sqrt{9 + 4} = \sqrt{13} = 3.606[/tex]
If you want to learn more, you can read:
https://brainly.com/question/12319416